Monilethrix. Case report. - Sotiriou, E.; Sotiriadis, D. (European Journal of Pediatric Dermatology, 2002)
Monilethrix or beading of hair is an inherited defect of the hair shaft. It precociously starts during the first months of life and then persists throughout life with little or, mostly, no improvement at all. We present a 4-year-old boy with monilethrix and discuss the different aspects of the disease.